Front Cover. Issue 1 (8th December 2022) - Moon, Sun Joon; Kim, Kyung‐Soo; Lee, Woo Je; Lee, Mi Yeon; Vigersky, Robert; Park, Cheol‐Young
Abstract : The cover image is based on the Original Article Efficacy of intermittent short‐term use of a real‐time continuous glucose monitoring system in non‐insulin–treated patients with type 2 diabetes: A randomized controlled trial by Sun Joon Moon MD et al., https://doi.org/10.1111/dom.14852